2020
DOI: 10.1037/law0000248
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of emotional stress on adult memory for single and repeated events.

Abstract: Victims of repeated incidents of abuse are often required to report incident-specific information about particular instances of the abuse. In the current study, we explored adults’ capability of such a task by examining the difference in memory for single versus repeated events that were either stressful or nonstressful. One hundred and twenty-two female participants engaged in either a single event or four highly similar events over a 4-week period. During each event, participants read and imagined themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
(143 reference statements)
3
19
0
Order By: Relevance
“…Adapting the methodological paradigm which is typically used in the child literature to an adult sample, Deck and Paterson (2019) found that adults who experienced a single event recalled significantly more correct details from the target session than adults who had experienced a repeated event. This finding that adults recalling a single event also report more correct details from the target session than those recalling a repeated event has been found in multiple experiments (Dilevski, Paterson, & van Golde, 2019; Theunissen et al, 2017). The tendency for both children and adults who recall a repeated event to have lower recall accuracy for variable details seems to be attributable to the fact that repeated‐event participants recall variable options which were experienced during one episode of the repeated event, but not the target episode (Connolly & Price, 2006; Deck & Paterson, 2019; Powell, Roberts, Ceci, & Hembrooke, 1999).…”
Section: Truth‐tellers' Memory For a Single And Repeated Eventsupporting
confidence: 77%
“…Adapting the methodological paradigm which is typically used in the child literature to an adult sample, Deck and Paterson (2019) found that adults who experienced a single event recalled significantly more correct details from the target session than adults who had experienced a repeated event. This finding that adults recalling a single event also report more correct details from the target session than those recalling a repeated event has been found in multiple experiments (Dilevski, Paterson, & van Golde, 2019; Theunissen et al, 2017). The tendency for both children and adults who recall a repeated event to have lower recall accuracy for variable details seems to be attributable to the fact that repeated‐event participants recall variable options which were experienced during one episode of the repeated event, but not the target episode (Connolly & Price, 2006; Deck & Paterson, 2019; Powell, Roberts, Ceci, & Hembrooke, 1999).…”
Section: Truth‐tellers' Memory For a Single And Repeated Eventsupporting
confidence: 77%
“…When accuracy was broadly defined as experienced details however, single and repeated‐event participants were equivalent in accuracy. This finding contributes to a small body of research which shows that child (Connolly, Gordon, Woiwod, & Price, 2016) and adult (Dilevski et al, 2020) repeated‐event witnesses do not report fewer correct details when accuracy is broadly defined. Despite the consistency of this finding across developmental levels, there are different legal expectations for children and adults.…”
Section: Discussionsupporting
confidence: 50%
“…A common methodological approach used to investigate adult repeated‐event memory in recent years has been an adaptation of the eyewitness paradigm, in which participants view one or multiple films (Theunissen et al, 2017; van Golde et al, 2017), or read a single or multiple accounts of a victim's perspective of abuse (Dilevski et al, 2020). Consistent with the results of the current experiment, these experiments have found that repeated‐event participants are less accurate when recalling details from the target event than single‐event participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations